Screening Nematoda Entomopatogen Isolat Jawa Timur Sebagai Agens Pengendali Hayati Serangga Hama Helicoverpa sp. Pada Tanaman Jagung - . NUGROHORINI; Arika PURNAWATI; Didik SULISTYANTO; . WAGIYANA (Jurnal Pengendalian Hayati, 2008)
Corn is the important food and crop for Indonesian. Recently, production of corn decreased because ofthe pest (Helicoverpa sp.). Until now, the control of Helicoverpa sp. depend on the using of chemicalelement. However, effect of synthetic chemical element usage was the appearance of secondary pest,the death of useful insect and the high accumulation of pesticide residue both in biotic and abioticagroecosystem. The residue of pesticide should effect on human health and environment balance.Furthermore, the control method using biological agents that have pathogenicity to host was done..One of biological agents is entomopathogenic nematodes. Entomopathogenic nematodes can kill it’shost at 24-72 hours, have wide host range such as Lepidoptera, Coleoptera, Diptera and Hymenopteraorder, and have no negatif effect on environment. The aim of the research is to find nematodes asbiological agents that effective against pest of corn (Helicoverpa sp.). The research was done inlaboratory of HPT UPN ”Veteran” Jawa Timur and HPT University of Jember. Methods of theresearch were : 1) Isolating entomopathogenic nematodes from many endemic area of Helicoverpaspp. In East Java; 2) Identificating Entomopatogenic Nematodes; 3) Screening IsolatesEntomopathogenic nematodes from East Java. The result indicated that there was anEntomopathogenic Nematodes Isolate from Tulungagung that has the highest pathogenicity (100%).